Comparative Analysis of the Efficiency, Safety, Predictability of Wavefront-Guided and Conventional FemtoLASIK Procedures in Low to Moderate Myopia - A. V. Doga; I. A. Mushkova; A. N. Karimova; E. V. Kechin; A. G. Guliev; V. G. Lee (Oftalʹmologiâ, 2018)
Purpose: to evaluate the effectiveness, safety, and predictability of the wavefront-guided FemtoLASIK using the Platoscan computer program and data from the KR-1W aberrometer, in comparison with the conventional algorithm FemtoLASIK in patients with low to moderate myopia.Patients and methods. There were 62 eyes of 62 patients with low to moderate myopia who had undergone FemtoLASIK procedure using an excimer laser ‘Microscan Visum” (Russia) and a femtosecond laser Femto LDV Z6 (Switzerland) in the study. In the “Wavefront” group which included 31 eyes with a mean spherical equivalent (SE) -=3,32 ± 1,23 D (M ± SD) was performed a wavefront-guided Femtosecond LASIK using aberrometer KR-1W (Japan) and a program for calculating the operation’s parameters “Platoscan” (Russia). “Standard” group included 31 eyes with an average SE –3.51 ± 1.21 D (M ± SD), who received the conventional FemtoLASIK. The “Wavefront” and “Standard” groups were comparable in terms of pre-operative data (age, sex, corneal curvature, central thickness of the cornea, sphere, cylinder, SE) (p > 0.05). All patients underwent complete ophthalmological examination before refractive laser surgery, and also patients were examined on the 1st day and 1 month after FemtoLASIK.Results. One month postoperatively, in the “Wavefront” group the UDVA 1.0 or better (20/20 or better by Snellen) was achieved in 93.5%, in the “Standard” group — in 96,8% (p > 0.05). There wasn’t observed a loss of the CDVA lines in both groups. In the “Wavefront” group, gain of one or more lines of the CDVA was in 38.7%, in the “Standard” group — in 12.9% (p = 0.04, Fisher’s exact test). In the “Wavefront” group the predictability of targeted refraction within ±0.5 D was in 93.5%, within ±1.0 D — in 100%, in the “Standard” group — in 90,3 and 100%, respectively (p > 0.05). The efficiency index in the “Wavefront” group was 1.00 (1.00; 1.20) (Me (Q25; Q75)), in the “Standard” group — 1.00 (1.00; 1,00) (Me (Q25; Q75)) (p > 0.05). The safety index in the “Wavefront” group was 1.00 (1.00; 1.20) (Me (Q25; Q75)), in the “Standard” group — 1.00 (1.00; 1,00) (Me (Q25; Q75)) (p > 0.05).Conclusions. The FemtoLASIK procedure, performed according to the conventional and wavefront-guided algorithms using the “Platoscan” computer program and data from the KR-1W aberrometer, is an effective, safe and predictable method for correcting low to moderate myopia, there is no statistically significant difference between two algorithms (p > 0.05).